The American duchess guide to 18th century beauty : 40 projects for period-accurate hairstyles, makeup and accessories - Stowell, Lauren; Cox, Abby; McKnight, Cheyney (Page Street Publishing Co., 2019)
"Ever wondered how Marie Antoinette achieved her sky-high hairstyle or how women in the 1700s created their voluminous frizz hairdos? The American Duchess Guide to 18th Century Beauty answers all your Georgian beauty questions--and teaches you all you need to know to recreate the styles yourself. Learn how to whip up your own pomatum and hair powder and correctly use them to take your 'dos to the next level. From there, dive into the world of buckles, hair cushions and papillote papers with historically accurate hairstyles straight from the 1700s. And top all your hair masterpieces with millinery from the time period, from a French night cap to a silk bonnet to a simple, elegant chiffonet. With Lauren and Abby's step-by-step instructions and insightful commentary, this must-have guide is sure to find a permanent place on the shelves of all 18th century beauty enthusiasts."--Amazon.com.